(untitled) (Journal of Economic Research & Business Administration, 2015)
The assessment of the competitive position of the Kazakhstan tourist industry in the global market is presented in the paper. Experience of other countries shows that to achieve competitiveness in the global tourism market is possible due to the development of new forms of economic integration between the state, business and tourist population. Therefore,the formation and the creation of favorable conditions for the effective functioning of the tourism cluster is one of the priorities of the state tourism policy of Kazakhstan. The dynamics of the development of the tourism sector of the economy of the Republic of Kazakhstan is analyzed in the research paper. The author stated factors for sustainable development of the tourism industry. Author reveals problems constraining the development of tourism in the country. The formation of tourist industry of Kazakhstan as one of the most important socio-economic areas, requires a certainstate regulation of economic relations and the state support the tourism industry.